Influence of Salinity on Growth and Phycoerythrin Production of Rhodomonas salina - Endar Marraskuranto; Tri J Raharjo; Rina S Kasiamdari; Tri R Nuringtyas (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2018)
Microalgae is a photoautotroph organism capable of producing various photosynthetic pigments with diverse beneficial properties. Rhodomonas salina, a Cryptophyte cell, contains only phycoerythrin as its phycobiliprotein pigment. The effects of salinity on growth and phycoerythrin concentration were investigated. Microalgae R. salina were grown in natural sea water with salinity of 33‰ and 50‰.The microalgae was batch-cultured in f/2 medium at light irradiation of 1100 lux, temperature of 24–26 oC, and photoperiode of 12 h : 12 h. The microalgae cell density was directly calculated using haemacytometer. The concentration of phycoerythrin was determined by spectrophotometric method. The cell density and phycoerythrin concentration were monitored every 4 days for 20 days of cell growth. Results showed that salinity did not affect significantly both on growth and phycoerythrin concentration extracted from R. salina biomass (p0.05; a = 0.05). At both salinity, maximum phycoerythrin concentration were reached on day 8. There was a positive correlation between cell density and phycoerythrin concentration from day 1 to day 8 of cell growth. Microalgae R. salina which was grown in natural seawater with salinity of 33‰ achieved the highest cell density of 8.4 x 105 cells/mL and the phycoerythrin concentration of 0.19 mg. 10-5 cell on day 8 of the culture. The highest phycoerythrin concentration was obtained on day 16 of the culture i.e 0.27 mg. 10-5 cell.Keywords: cell density, growth media, phycoerythrin, Rhodomonas salina, salinity